Application of Efficient Express Sequence Tags Information for Classification and Functional Study of Simple Sequence Repeats in Cattle Testis Tissue - M. Manavipour; A. Ehsani; A. A. Masoudi (Faculty of Animal Science, Bogor Agricultural University, 2020)
Genomic markers play an important role in tracing the flow of genetic causality of observable signals in animals and plants. In farm animals, the participation of male animals in the gene pool of subsequent generations are much higher than female animals and testes are the most important organs of the male reproductive system. This study was conducted to investigate simple sequence repeats (SSR) within the expressed sequence tags (ESTs) in order to classify the Bos taurus testis tissue’s genes for their relationship and specificity with related reproductive domains. A total of 48,549 publicly available EST sequences from cattle testis tissue downloaded from GenBank database, out of which, 10,237 sequences that their library made from testis tissue were extracted and specialized as the studied sequences using several searching tools and software. Across these selective sequences, 2,039 contigs, 5,097 singletons, and 153 SSRs were detected. EST-SSRs were subsequently evaluated using GenBank and categorized based on their functions in biological systems of dairy cattle. Investigation of these motifs showed that the identified EST-SSRs can be classified into 48 types that GT in dinucleotides and GCC in trinucleotides had the highest frequency. Annotation and gene ontology analysis revealed a relationship among 54 domains with the observed SSRs. Localization and characterization of such markers can help tracing the production of amino acids coded by identified repeats as shown in this study.